HIGH-TEMPERATURE SUPERCONDUCTORS - Dilafruz Dusiyarovna Qurbonova (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
Research in the field of high-temperature superconductors is one of the important areas of science and technology. High-temperature superconductor materials provide great opportunities for lossless transmission of electric energy, magnetic levitation technologies, and the creation of highly efficient energy storage systems. This article examines the possibilities of proposing scientific innovations related to high-temperature superconductor materials.